microRNA-377 Signaling Modulates Anticancer Drug-Induced Cardiotoxicity in Mice - Henderson, John; Dubey, Praveen K.; Patil, Mallikarjun; Singh, Sarojini; Dubey, Shubham; Namakkal Soorappan, Rajasekaran; Kannappan, Ramaswamy; Sethu, Palaniappan; Qin, Gangjian; Zhang, Jianyi; Krishnamurthy, Prasanna (Frontiers in Cardiovascular Medicine, 2021)
Doxorubicin (DOX, an anthracycline) is a widely used chemotherapy agent against various forms of cancer; however, it is also known to induce dose-dependent cardiotoxicity leading to adverse complications. Investigating the underlying molecular mechanisms and strategies to limit DOX-induced cardiotoxicity might have potential clinical implications. Our previous study has shown that expression of microRNA-377 (miR-377) increases in cardiomyocytes (CMs) after cardiac ischemia-reperfusion injury in mice, but its specific role in DOX-induced cardiotoxicity has not been elucidated. In the present study, we investigated the effect of anti-miR-377 on DOX-induced cardiac cell death, remodeling, and dysfunction. We evaluated the role of miR-377 in CM apoptosis, its target analysis by RNA sequencing, and we tested the effect of AAV9-anti-miR-377 on DOX-induced cardiotoxicity and mortality. DOX administration in mice increases miR-377 expression in the myocardium. miR-377 inhibition in cardiomyocyte cell line protects against DOX-induced cell death and oxidative stress. Furthermore, RNA sequencing and Gene Ontology (GO) analysis revealed alterations in a number of cell death/survival genes. Intriguingly, we observed accelerated mortality and enhanced myocardial remodeling in the mice pretreated with AAV9-anti-miR-377 followed by DOX administration as compared to the AAV9-scrambled-control-pretreated mice. Taken together, our data suggest that in vitro miR-377 inhibition protects against DOX-induced cardiomyocyte cell death. On the contrary, in vivo administration of AAV9-anti-miR-377 increases mortality in DOX-treated mice.